Systematic Analysis and Validation of the Prognosis, Immunological Role and Biology Function of the Ferroptosis-Related lncRNA GSEC/miRNA-101-3p/CISD1 Axis in Lung Adenocarcinoma - Jiang, Xiulin; Yuan, Yixiao; Tang, Lin; Wang, Juan; Zhang, Dahang; Duan, Lincan (Frontiers in Molecular Biosciences, 2022)
Lung adenocarcinoma (LUAD) is the most common type of lung cancer, accounting for approximately 85% of pulmonary malignancies. Emerging evidence has demonstrated that ferroptosis plays a central role in both immunities as well as tumor proliferation. However, the clinical significance, immunological function, and upstream modulatory mechanism of ferroptosis-related genes in LUAD remain unclear. Here, we utilized various bioinformatics data to identify differentially expressed (DEGs) and prognosis-related ferroptosis (FRGs) genes in LUAD. Based upon identified DEGs, FRG, and ceRNA modulatory networks were constructed. Pearson’s correlation analysis was used to evaluate the correlation between FRGs and the tumor mutational burden, microsatellite instability, tumor-infiltrating immunity, cellular checkpoint control, and drug sensitivity in LUAD. A loss-of-function analysis was performed to verify the function of CISD1 in LUAD progression. Our findings revealed that certain FRGs (CISD1, ATP5MC3, PGD, SLC7A11, ACSL3, and FANCD2) are significantly upregulated in LUAD and that their elevated expression is associated with both advanced tumor stage and unfavorable prognosis. Furthermore, Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment results revealed these FRGs to be primarily involved in ferroptosis and glutathione metabolism in LUAD. We constructed a prognostic FRG-based model capable of accurately predicting LUAD patient overall survival with high specificity. The upstream lncRNA GSEC/miRNA-101-3p regulatory axis involving CISD1, ATP5MC3, and PGD was identified to be relevant in tumor progression. We also found GSEC, CISD1, ATP5MC3, and PGD to be upregulated, with miRNA-101-3p downregulated, in the setting of LUAD. Immunohistochemical analysis revealed CISD1, ATP5MC3, and PGD overexpression in LUAD tissue samples; CISD1 knockdown was noted to significantly inhibit LUAD proliferation and migration. In summary, this study characterizes relevant functional roles of the lncRNA GSEC/miR-101-3p axis in the setting of LUAD and suggests diagnostic and therapeutic biomarkers potentially useful in the clinical management of this illness.